First Report of Botryosphaeria dothidea Responsible for Branch Dieback and Canker on Hovenia dulcis in South Korea - 이동현; Ji-Won Park; Chul-Woo Kim; 권춘근; 김성학 (Journal of forest and environmental science , 38(2), 2022)
In 2021, severely infected trees showing distinct symptoms including branch dieback, necrotic lesions on branches, cankers on the shoots, and dark brown discoloration on the stem on Hovenia dulcis were found in the provincial forest of Jeollabuk-do located in Jangsu, South Korea. The causal agent of the pathogen was identified as Botryosphaeria dothidea based on morphology and sequence comparisons. This is the first confirmed report of B. dothidea causing branch dieback and canker on H. dulcis. KCI Citation Count: 0